Synthesis, Molecular Docking and Pharmacological Evaluation of Some New Schiff and Mannich Bases of 5-Methylisatin Derivatives - Mondal, Prasenjit; Samajdar, Saptarshi; Khamkat, Piyali; Barik, Vivek; Mandal, Sudip Kumar (Asian Journal of Chemistry, 2024)
Two novel series of Schiff and Mannich based 5-methylisatin were synthesized by Mannich reactions and evaluated for anthelmintic and antibacterial activities. The Mannich bases were synthesized from the Schiff base using various secondary amines and formaldehyde along with the derivatives of piperazinyl groups. N-Methyl piperazinyl (ICP-2B and ICM-2B) and piperidinyl derivatives (ICP-2C and ICM-2C) were found to have a highly significant anthelmintic potential. For compound ICP-2B, the paralysis time was observed at 4.936 ± 0.12 min at low concentration (0.1 % w/v) and 1.95 ± 0.10 min at high concentration (1% w/v). At low concentration (0.1%), compound ICM-2B, the paralysis time is 4.43 ± 0.17 min; at high concentration (1% w/v), it is 1.675 ± 0.08 min. These data indicated that compounds ICP-2B and ICM-2B has immense potential as anthelminthic and antimicrobial drug in future. Moreover, the in vitro study was confirmed by molecular docking studies, indicating both compounds ICP-2B and ICM-2B can find its use as novel drug against various pathogenic helminthes and bacteria.